Metabolizable energy: sulfurous amino acids ratio for light laying hens in the growth stages (Research, Society and Development, 2021)
The level of metabolizable energy (EM) and methionine + digestible cystine (dMetCys) was determined for light laying hens in the phases from 1 to 6 weeks and from 7 to 12 weeks of age. The experimental design was completely randomized, distributed in a factorial scheme with 3 levels of dMetCys (0.576%, 0.640% and 7.04% in the phase from 1 to 6 weeks of age and 0.447%, 0.497% and 0.547%) x 3 levels of MS (2,755; 2,900 and 3,045 kcal / kg), totaling 9 treatments. Performance data, serological data and histomorphometry of the small intestine were analyzed. In the 1-to-6-week phase, the combination of 0.640% dMetCys with 2,755 kcal / kg of MS, as well as 0.704% dMetCys associated with 3,045 kcal / kg of MS promoted better results, showing that a higher level of dMetCys indicates greater demand for IN. The slaughter variables and serological analyzes were more satisfactory with the level of 0.640% of dMetCys associated with 2,755 kcal / kg of ME. For the 7-to-12-week phase, no statistical effects were observed for the performance variables, but there was a higher absolute weight for liver and spleen in diets with higher MS, and a higher absolute weight for Fabricius Bursa in the treatment with lower levels of dMetCys and IN. There was no hepatic steatosis in any of the studied phases. 0.640% dMetCys associated with 2755 kcal / kg EM is recommended for chickens between 1 and 6 weeks of age, and 0.447% dMetCys associated with 2,900 kcal / kg EM during the growth phase (7 to 12 weeks of age).